Erythema Ab Igne Successfully Treated With Mesoglycan and Bioflavonoids: A Case-Report - Gianfaldoni, Serena (Open Access Maced J Med Sci, 2017)
Erythema ab igne is a localised, cutaneous condition consisting of reticulate hyperpigmentation, epidermal atrophy, and telangiectasias. It is caused by repetitive and prolonged exposure to moderate heat that is insufficient for producing burns. Currently, erythema ab igne is most commonly observed following repeated use of hot water bottles, infrared lamps and heating pads. If not properly treated, erythema ab igne can become chronic and even malignant. We report a case of erythema ab igne, successfully treated with systemic mesoglycan-based therapy, and local therapy with bioflavonoids.